Analisis Kualitas Pelayanan Penumpang Angkutan Laut di Pelabuhan Yos Soedarso Tual Maluku - Rumlus, Wisnu; Akhmad, Ekka Pujo Ariesanto (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2022)
Service is a person's or agency's business that aims to serve the needs of service users. Service is a very important element in an effort to increase satisfaction for service users. This study aims to determine the effect of passenger service quality on passenger satisfaction partially at the port of Yos Soedarso Tual Maluku. This research is included in the category of research that uses a quantitative approach. The population is 30 port service users, Yos Soedarso Tual Maluku, while the number of samples is the same as the population. The sampling technique is saturated sampling. Data collection techniques using questionnaires, while data analysis using simple linear regression analysis. The results of the study indicate that there is a significant influence between the quality of passenger service on satisfaction, it is shown from: 1). The results of the t-test at a constant of 0.485 with a significance of 0.632. 2). There is a significant influence between service effectiveness. The results of the t-test of 11.554 with a significance of 0.000. 3). There is a significant influence between passenger service partially on passenger satisfaction and the regression equation Y = 1.251 + 0.909 X